Willingness to vaccinate and willingness to pay for vaccination against peste des petits ruminants in northern Senegal - Ilboudo, Guy Sidwatta; Wanyoike, Francis; Bahta, Sirak; Sy, Samba; Djigo, Cheikh Ahmed Tidiane; Sall, Papa Anoune; Lô, Mamadou Moustapha; Dione, Michel (Frontiers in Veterinary Science, 2024)
This study was carried out in the Linguere department, Louga region of Senegal. Its objective was to , explore the socio-economic factors that influenceing small ruminant producers' decisions on vaccination against Ppeste des petits ruminants vaccination. We carried out aWith a focus on Willingness willingness to vVaccinate and wWillingness to pPay for vaccination using a choice experiment methodology approach with 200 small ruminant producers. Results highlight showed tahtthatthe key factors that influenceing willingness to vaccinate, includeing perceived benefits of vaccination (98, 95%CI: 96-100%), type of vaccinator type (91, 95%CI: 87-95%), access to information (86, 95%CI: 81-91%), vaccine availability (80, 95%CI: 74-86%), and possession of a vaccination certificate by the producer (76, 95%CI: 70-82%). Preferences of producers leaned towards home vaccination (preference weight = 0.74, P = 1%), separate individual herd vaccination (preference weight = 0.45, P = 1%), elective participation (preference weight = 0.33, P = 1%0.01), and low-cost services (preference weight = -0.004, P = 1%0.1). Producers expressed a willingness to pay for vaccination per animal of XOF 184 (USD 0.3), XOF 113 (USD 0.18), and XOF 82 (USD 0.13) for home, individual herd, and elective vaccination, respectively. Notably, indifference was observed regarding the nature of the vaccine nature and combinations of vaccination with other services. The findings underscore the importance of targeted awareness campaigns and bringing vaccination services closer to small ruminant producers.